PENGAKARAN IN VITRO EKSPLAN TEBU (Saccharum officinarum, L.) VARITAS BULULAWANG PADA BERBAGAI KONSENTRASI NAA DAN SUKROSA TERHADAP PERTUMBUHAN PLANLET TEBU - Ardika Ageng Samudera; Hadi Rianto; Historiawati Historiawati (Universitas Tidar, 2019)
A study about the effect of NAA concentrations and sucrose concentrations on in vitro rooting to sugarcane explant growth (Saccharum officinarum, L.) Bululawang varities was conducted on 2 April until 23 July 2018 at Balai Benih Tanaman Perkebunan Kota Salatiga. Research methods that were used is factorial arrangement (4×4) with a completely randomized block design and five replications as block. First factor, four concentration levels of NAA (0; 2,5; 5; and 7,5 mg/l) and second factor, four concentration levels of sucrose (0; 25; 50; and 75 g/l). The result showed NAA concentration level increased number of roots per explant, but decreased fresh weight of leaves per explant and dry weight of leaves per explant. However, 4,7 mg/l NAA concentration level give highest fresh weight of roots per explant and 5,2 mg/l NAA concentration level give highest dry weight of roots per explant. Sucrose concentration level increased dry weight of leaves per explant, fresh weight of roots per explant and dry weight of roots per explant. However, 59 g/l sucrose concentration level give highest number of roots per explant, 46 g/l sucrose concentration level give highest number of shoots per explant, 46 g/l sucrose concentration level give highest number of leaves per explant and 61 g/l sucrose concentration level give highest fresh weight of leaves per explant. NAA concentration level and 50 g/l sucrose concentration level increased number of roots per explant, but NAA concentration level and 75 g/l sucrose concentration level decreased dry weight of leaves per explant. 4,1 mg/l NAA concentration level and 75 g/l sucrose concentration level give highest fresh weight of roots and 4,9 mg/l NAA concentration level and 75 g/l sucrose concentration level give highest dry weight of roots per explant.